The difference in CD4+ T cell immunity between high- and low-virulence Tembusu viruses is mainly related to residues 151 and 304 in the envelope protein - Meng, Runze; Yang, Baolin; Feng, Chonglun; Huang, Jingjing; Wang, Xiaoyan; Zhang, Dabing (Frontiers in Immunology, 2022)
Tembusu virus (TMUV) can result in a severe disease affecting domestic ducks. The role of T cells in protection from TMUV infection and the molecular basis of T cell-mediated protection against TMUV remain largely uncharacterized. Here, we used the high-virulence TMUV strain Y and the low-virulence TMUV strain PS to investigate the protective role for TMUV-specific CD4+ and CD8+ T cells. When tested in a 5-day-old Pekin duck model, Y and PS induced comparable levels of neutralizing antibody, whereas Y elicited significantly stronger cellular immune response relative to PS. Using a duck adoptive transfer model, we showed that both CD4+ and CD8+ T cells provided significant protection from TMUV-related disease, with CD8+ T cell conferring more robust protection to recipient ducklings. For TMUV, CD4+ T cells mainly provided help for neutralizing antibody response, whereas CD8+ T cells mainly mediated viral clearance from infected tissues. The difference in T cell immunity between Y and PS was primarily attributed to CD4+ T cells; adoptive transfer of Y-specific CD4+ T cells resulted in significantly enhanced protective ability, neutralizing antibody response, and viral clearance from the brain relative to PS-specific CD4+ T cells. Further investigations with chimeric viruses, mutant viruses, and their parental viruses identified two mutations (T151A and R304M) in the envelope (E) protein that contributed significantly to TMUV-specific CD4+ T cell-mediated protective ability and neutralizing antibody response, with more beneficial effects being conferred by R304M. These data indicate T cell-mediated immunity is important for protection from disease, for viral clearance from tissues, and for the production of neutralizing antibodies, and that the difference in CD4+T cell immunity between high- and low-virulence TMUV strains is primarily related to residues 151 and 304 in the E protein.